2006
DOI: 10.1128/cvi.00151-06
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccine UsingMycobacterium bovisAg85B Antigen Induces Partial Protection against Experimental Infection in BALB/c Mice

Abstract: Bovine tuberculosis is a major cause of economic loss in countries where it is endemic, and in some countries, it may be a significant zoonotic disease problem. Therefore, new strategies for vaccine development are required, and among them, genetic immunization has potential value. The main goal of this study was to test the Mycobacterium bovis Ag85B gene as a DNA vaccine following challenge with an M. bovis virulent strain (ATCC 19274). Groups of BALB/c mice (n ‫؍‬ 10) were immunized four times intramuscularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…The above results indicate that, although AM was detected in all Mtb strains, the distribution of epitopes on the surfaces of these strains was different, a finding which may have important implications in developing vaccines and serodiagnostic tests. Some of the specific mycobacterial antigens (HBHA, a-crystallin, Ag85 complex) that induce protective antibody responses [32][33][34][35][36][37][38][39] are given in Table 1.…”
Section: Mouse Modelmentioning
confidence: 99%
“…The above results indicate that, although AM was detected in all Mtb strains, the distribution of epitopes on the surfaces of these strains was different, a finding which may have important implications in developing vaccines and serodiagnostic tests. Some of the specific mycobacterial antigens (HBHA, a-crystallin, Ag85 complex) that induce protective antibody responses [32][33][34][35][36][37][38][39] are given in Table 1.…”
Section: Mouse Modelmentioning
confidence: 99%
“…Hence, in addition to measuring systemic‐level IFN‐γ responses in the present study, we also sought to identify any vaccine‐mediated pulmonary protection induced by the DNA immunization by challenging mice via aerosol exposure to virulent M. bovis . Previous studies have indicated that DNA‐based vaccines in rodents have the potential to confer measurable protection against M. bovis 10 , 11 , 27 . In these studies, one major measure of protection was to observe a post‐challenge reduction in pathogen burdens among vaccinees; the same measurement was used here as the means of assessing any vaccine‐mediated protection against M. bovis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that DNA-based vaccines in rodents have the potential to confer measurable protection against M. bovis. 10,11,27 In these studies, one major measure of protection was to observe a postchallenge reduction in pathogen burdens among vaccinees; the same measurement was used here as the means of assessing any vaccinemediated protection against M. bovis. However, in the present study, the only vaccine treatment that conferred significant protection against pulmonary M. bovis challenge was BCG immunization, indicating that the DNA vaccination regime used here is not, on its own, a suitable alternative to the current TB vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The use of costimulatory molecule CD 154 along with ESAT-6 gene has been suggested to enhance the immunogenic properties of mycobacterial DNA vaccines. Further, M. bovis Ag85B gene has been found suitable while incorporating in plasmid vector due to its ability to induce a Th1 type of immune response (Teixeira et al 2006). Aside to this, recently, DNA vaccines used in combination with Bacillus Calmette Guerin (BCG) elicited superior protection during challenge studies (Cai et al 2006 Against viral diseases of bovines, the earliest reports suggest the use of a gene encoding the VP4 protein of bovine rotavirus (BRV), found effective in stimulating a Th1-like immune response (Suradhat et al 1997).…”
Section: Applications Of Nucleic Acid Vaccines In Veterinary Practicementioning
confidence: 99%